THE PROTECTION OF PRIVACY AND TRUST: THE ROLE OF THE PRINCIPLE OF CONFIDENTIALITY IN INDIVIDUAL COUNSELING - Fauziah, Hana; Budiman, Nandang; Aulia Nadhirah, Nadia (Jurnal Bimbingan Konseling dan Psikologi, 2025)
This research explores the important role of confidentiality in individual counseling, focusing on its impact on trust between counselor and counselee. The main objective is to illustrate how maintaining confidentiality fosters a safe environment for counselees to openly discuss sensitive issues. Using the Systematic Literature Review (SLR) methodology, this study reviewed existing literature to gather insights on the principles of confidentiality in counseling practice. This approach ensures that findings are well-supported and objective, overcoming the challenge of maintaining objectivity in literature reviews. The results showed that confidentiality is essential for building trust. When counselors adhere to confidentiality guidelines, counselees are more likely to engage openly, which increases the effectiveness of counseling sessions. Conversely, breaches of confidentiality can cause emotional distress and undermine trust, thus making the counselee hesitant to seek help. This discussion emphasizes the need for counselors to receive specialized training in ethical practices, especially regarding confidentiality, to reduce the risks associated with potential breaches. In conclusion, this study underscores confidentiality as a basic element that protects the privacy of counselees and enhances counseling effectiveness. The authors recommend that counseling programs include comprehensive training on ethical standards and confidentiality practices to better prepare counselors for their roles. In addition, ongoing educational initiatives should reinforce the importance of these principles in fostering a trusting counselor-counselor relationship. Keywords: privacy and trust, confidentiality, individual counseling